Pay Knowledge and Referents in a Tiered-Employment Setting - Martin, James; Lee, Raymond (Relations industrielles / Industrial Relations, 1992)
This study examines both the main and the interaction effects of knowledge of the pay structure and social and self pay referents on pay attitudes in a setting with wage andjobduty tiers. Knowledge of the pay structure when hired and expected pay were among the most important predictors of pay fairness and pay satisfaction. The significant interaction effects found across tier levels indicated pay knowledge had a differential impact on pay attitudes. The interaction effects, however, did not support the assumption that the reason attitudes differ among employees on various tier levels is that they use différent referents.